ANALYSIS OF THE EFFECTS OF QUALITY WORK OF LIFE FACTORS ON EMPLOYEE MOTIVATION REGIONAL OFFICE OF UNIVERSITAS TERBUKA AT PANGKALPINANG, INDONESIA - Yusuf Yusuf; Adrian Sutawijaya (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
The purpose of this research is to know the description of Quality of Work Life and Employee Motivation in UPBJJ-UT Pangkalpinang, and its influence is partially and simultaneously so that it can get information to increase motivation which will improve the quality of organizational performance. The research method used is descriptive quantitative approach with cross sectional design. The sample in this study amounted to 30 samples. The type of data used is the primary data. Data analysis technique using multiple linear regression test. The results showed that (1) The overall variables had a high average value that is in the category of 3.41-4.20 and the variable of pride to the institution had the highest average value of 4.21%. Thus the majority of respondents feel proud of the institution while working at UPBJJ-UT Pangkalpinang. In general, there are seven variables that have positive and significant influence and four variables that have positive but not significant influence. Variables that have positive and significant impacts are available facilities, workplace safety, employee engagement, communication, security, a sense of pride in institutions and work restructuring. While the variables that have positive but not significant are balanced compensation, career development, problem solving and work environment (3) Simultaneously the Quality of Work Life variable has a positive and significant influence on work motivation. This means that any increase or decrease in Quality of Work Life together will give a significant influence on employee motivation in UPBJJ-UT Pangkalpinang. Keywords: Quality of Work Life, Work Motivation, and Employee Motivation